2022
DOI: 10.3889/oamjms.2022.9393
|View full text |Cite
|
Sign up to set email alerts
|

Patient Autonomy, Decision-making and Cultural Impact in Elder Care in Albania

Abstract: BACKGROUND: Maintaining patients’ autonomy and including them in the decision-making process is crucial in eldercare. This study explores the cultural impact of independence in Albanian nursing homes. This paper follows previous publications from the same project. AIM: Based on the previous research on ethical and legal issues, the aim was to identify how and why autonomy is frequently compromised. METHODS: An exploratory qualitative study with semi-structured interviews and field notes was conducted. The fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In such situations, participants emphasized that they cannot protect the rights of elderly residents, most of whom are placed in institutions against their will and without their consent. Family members make decisions, although older people have the right to information, choice, and approval following relevant regulations and laws [ 9 ]. Despite the various conflicts nurses can encounter with colleagues or families, the importance of nurses’ ability to guarantee and protect the rights and wishes of older people in the centers where they work has been described and highlighted in earlier studies [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In such situations, participants emphasized that they cannot protect the rights of elderly residents, most of whom are placed in institutions against their will and without their consent. Family members make decisions, although older people have the right to information, choice, and approval following relevant regulations and laws [ 9 ]. Despite the various conflicts nurses can encounter with colleagues or families, the importance of nurses’ ability to guarantee and protect the rights and wishes of older people in the centers where they work has been described and highlighted in earlier studies [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, there are only a few social workers and nursing assistants, even though the profession of social worker and nursing assistant is provided for in the authorized structure [ 3 , 4 ]. This occurs because neither university curricula nor training institutions in Albania provide adequate training for nursing assistants and social workers in caring for older people [ 8 , 9 ]. Nurses are considered the backbone of the healthcare system in providing essential healthcare services to the population.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Health care professionals play a significant role in combating this health problem, particularly when patients suffer from severe symptoms that require hospital admission for treatment or even palliative care, as the main providers of end‐of‐life care. Several studies have demonstrated that nurses and nurse‐assistants experience pressure, burden, and emotional challenges concerning an increase in patient deaths (Hanna et al, 2021a , 2021b ; Podgorica, Flatscher‐Thöni, et al, 2021 ; Podgorica, Pjetri, et al, 2021 ; Podgorica, Shabani, et al, 2022 ) and insufficient resources to provide care (Mehta et al, 2021 ; Podgorica, Shabani, et al, 2022 ; Podgorica, Zenzmaier, et al, 2022 ). Previous studies focused on emotional and psychological distress that affected health care professionals' well‐being (Huang et al, 2020 , 2021 ; Mitchinson et al, 2021 ; Rathnayake et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%